Analysis, design and development of a software prototype for the administration of parking lots (2020)
(Eng) This Project was born because of the needing of a software that simplifies the administration of a parking establishment, in a way that many of the characteristics of this establishments could be set from a software tool. In this project, a desktop app was designed and developed, that works on some Windows versions (7, 8, 8.1, 10), and allows the administration, setting up, and execution of the tasks performed in a parking establishment, with extended characteristics like inventory lending (helmets, etc.) and the creation of parking sites. The prototype has been developed in the Windows platform to take advantage of the basic infrastructure of a parking in Pereira city. The software conception includes activities like client management, employees, complaints, vehicles, monthly installments, incomes, expenses, binnacle, audit, inventory, lending, and billing. In order to develop the prototype, a client/server architecture was used, in order to have the different PCs connected to the same database, sharing between them every management. The IDE WINDEV was used, and the language WLANGUAGE was used for development.